Nanoscale synthesis, structural elucidation, DFT, and biological activity of amide appended transition metal(II) macrocyclic complexes in drug delivery system. Issue 19 (17th December 2022) - Patyal, Meenakshi; Κaur, Kirandeep; Sharma, Promila; Gupta, Nidhi; Malik, Ashok Kumar; Paul, Kamaldeep
Abstract: Nanoscale complexes of Mn(II), Ni(II), and Cu(II) with 6, 15-diamino-1, 4, 9, 12-tetraazacyclohexadecane-5, 8, 13, 16-tetraone were synthesized by ultrasonic sonication method. The Fourier-transform infrared (FTIR) spectroscopy, ultraviolet–visible (UV–vis) spectroscopy, carbon, hydrogen, and nitrogen elemental (CHN) analysis, mass spectrometry (MS), and electron spin resonance (ESR) spectroscopy were used to identify and suggest the structure of the synthesized nanocomplexes. The field emission scanning electron microscopy (FE-SEM) and powder X-ray diffraction (PXRD) revealed that the size of the synthesized nanocomplexes was 44–58 nm. Based on these studies, hexagonal, monoclinic, and cubic unit cell structure has been proposed for the synthesized Mn(II), Ni(II), and Cu(II), respectively. The theoretical calculations of the synthesized nanocomplexes were carried out by a GAUSSIAN 09 program involving geometry optimization and bond parameters using the B3LYP method. Moreover, binding energy, HOMO, and LUMO have been calculated. In addition, hardness, softness, chemical potential, and dipole moment were calculated for ligand and its metal nanocomplexes. The biological efficacy of the synthesized nanocomplexes was examined and found to be better and highly effective drug delivery system (DDS) for the antimicrobial and antioxidative agent. Abstract : UF0001